UNION WAGE COMPRESSION AND SKILL ACQUISITION - Aksoy, Tolga (WILEY, 2019)
In this paper, I examine the relationship between unionisation and total output in an economy with a dual labour market, heterogeneous agents, and human capital investment. My primary focus is the skill acquisition channel, through which unionization affects total output. I theoretically demonstrate that the skill premium, and thus human capital investment, is determined by the prevalence of unions in high- or low-skill-intensive sectors. In particular, if a low (high)-skill sector is unionised, then the skill premium is higher (lower), ensuring a larger (smaller) high-skill sector, irrespective of the unions bargaining power. To test this hypothesis, I also empirically investigate the effects of unionisation on total productivity. The results indicate that through the reallocation of labour, unionisation induces an expansion of high-skill-intensive sectors, while low-skill-intensive sectors contract.
Keywords: dual labour market; human capital; occupational choice; unions; E24; J24; J31; J51; LABOR-MARKET INSTITUTIONS; EMPLOYMENT PROTECTION; INEQUALITY; FINANCE; GROWTH; PANEL; Business & Economics